Controllable microstructure tailoring for regulating conductivity in Al-doped ZnO ceramics. Issue 2 (February 2020) - Sun, Qianying; Li, Guorong; Tian, Tian; Man, Zhenyong; Zheng, Liaoying; Barré, Maud; Dittmer, Jens; Goutenoire, François; Kassiba, Abdel Hadi
Abstract: Structural and electrical behavior of Al2 O3 doped ZnO-based ceramics were investigated as function of the aluminum doping ratios under reducing sintering atmosphere (N2 +CO). With Al2 O3 doping from 0.1 mol% to 0.55 mol%, the electrical conductivity increases firstly to a maximum (1.52 × 10 5 S·m −1 ) at 0.25 mol%, and then decreases gradually. The increased conductivity is explained by the formation of shallow donors as AlZn -Zni complexes with doping to 0.25 mol%. As Al2 O3 doping further increasing to 0.55 mol%, ZnAl2 O4 spinel phase and more ZnO-ZnO grain boundaries are formed, hindering charge carriers transport, to decrease charge carrier mobility, thus to decrease the conductivity of ZnO ceramics. Therefore, the AlZn -Zni complexes, grain boundaries and ZnAl2 O4 spinel can be adjusted by doping different Al2 O3 amount, thus the carriers' concentration and their mobility are optimized to increase the conductivity. Our work, as a fundamental research, is of great significance to control conductivity by regulating Al2 O3 doping.